Pengaruh Online Customer Review terhadap Keputusan Pembelian pada Marketplace Shopee di Kalangan Mahasiswa Kota Bandung - Kusuma, Ibnu Sastra Hadi (International Journal Administration, Business & Organization, 2023)
This study aims to determine the effect of Online Customer Reviews on purchasing decisions at the Shopee Marketplace among Bandung City University Students. Respondents came from Bandung city students who had made purchases and viewed review pages on the Shopee Marketplace. This research uses descriptive quantitative methods, validity and reliability tests, normality tests, and data analysis using simple linear regression. The sample in this study were 125 respondents. Data collection was carried out by distributing questionnaires to respondents using Google Form. The results of the study show that online customer reviews have a very significant effect on purchasing decisions which means that online customer reviews can improve purchasing decisions.